Pemanfaatan Podcast Youtube TVRI Jawa Barat untuk Meningkatkan Citra Lembaga Penyiaran Publik - Pingkan, Virisya Olivia; Lubis, Ira Aryanti Rasyi (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
This qualitative case study research analyzes TVRI West Java’s strategy in utilizing youtube podcasts to build a positive image as a Public Broadcasting Institution (LPP). Furthermore, this study identifies the challenges and successes in integrating digital content. Data was gathered through in-depth interviews with the new media content management, observation of the podcasts content, and documentation studies, then analyzed using data reduction, display, and conclusion drawing, and validated by triangulation. The results indicate that the utilization of youtube podcasts is a highly effective media convergence strategy. The platform not only disseminates content but also successfully creates a new image that is more modern, relevant, and accessible, especially among the young audience. This strategy significantly strengthens TVRI West Java’s position amid digital media competition, demonstrating the LPP’s adaptability, and allows for a more personal reach to the audience.